2018
DOI: 10.1007/s10086-018-1738-4
|View full text |Cite
|
Sign up to set email alerts
|

Moisture-dependent orthotropic viscoelastic properties of Chinese fir wood in low temperature environment

Abstract: The influence of moisture content (MC) on the orthotropic viscoelasticity of Chinese fir wood (Cunninghamia lanceolata [Lamb.] Hook.) has been examined in low temperature environment. Storage modulus E′ and loss modulus E″ of wood with six different levels of MC ranging from 0.6 to 22.0% were determined from − 120 to 40 °C and at multi-frequency range of 0.5, 1, 2, 5, and 10 Hz using a TA instruments ® Dynamic Mechanical Analyzer (DMA 2980). The results showed that a distinct moisture dependency is exhibited b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…Further complicating the hemicelluloses glass transition question are DMA experiments performed over temperature and moisture conditions in which the expected hemicelluloses glass transition is not observed. As previously mentioned, Li et al [217] observed hemicelluloses glass transitions when their specimens were oriented such that the tensile stresses were being applied in in radial and tangential wood orientations, but not the longitudinal orientation. Jakes [32] also performed nanoindentation in the transverse plane of the S2 in which the loads are applied parallel to the cellulose fibrils, but no thermal transition was observed in that orientation.…”
Section: Hemicelluloses and Amorphous Cellulose Glass Transitionsmentioning
confidence: 86%
See 3 more Smart Citations
“…Further complicating the hemicelluloses glass transition question are DMA experiments performed over temperature and moisture conditions in which the expected hemicelluloses glass transition is not observed. As previously mentioned, Li et al [217] observed hemicelluloses glass transitions when their specimens were oriented such that the tensile stresses were being applied in in radial and tangential wood orientations, but not the longitudinal orientation. Jakes [32] also performed nanoindentation in the transverse plane of the S2 in which the loads are applied parallel to the cellulose fibrils, but no thermal transition was observed in that orientation.…”
Section: Hemicelluloses and Amorphous Cellulose Glass Transitionsmentioning
confidence: 86%
“…They did not report any water loss tests for higher temperatures. Both Jiang and Lu [216] and Li et al [217] report that up to 40 °C in their experiments the MC changed less than 0.5%. The specimen cross-section and heating rate are the two most likely experimental parameters that will affect the specimen drying during the temperature scans.…”
Section: Hemicelluloses and Amorphous Cellulose Glass Transitionsmentioning
confidence: 89%
See 2 more Smart Citations
“…In addition, Backman and Lindberg (2001), and Li et al (2018b) reported a small peak at around room temperature or even below ambient temperatures when the wood MC ranged from around 3 to 14.1%. Li et al (2018b) assumed that this small peak was attributed to the melting of frozen water. Backman and Lindberg (2001) and assumed that the small peak was attributed to the glass transition of hemicellulose.…”
Section: Introductionmentioning
confidence: 97%